PERBANDINGAN METODE EOQ DAN JIT DALAM MENGANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU - Bambang Pujo Purwoko; Ahmad Gilang Permana Putra (The Asia Pacific Journal Of Management Studies, 2017)
As business group (Kelompok Usaha Bersama) that moved in food business field, the used raw material at KUB Mitra Mandala Sobang is brown sugar (gula aren) that will be made become powder which is often called by palm sugar (gula semut). In conducting the availability of raw material, some challenges that faced by this company is financial controlling such as the differentiate of raw material price, the storage of raw material with damaging risk, not optimal production process and the unfilled number of raw material.In this research, the writer is reviewing the controlling of the raw material availability at KUB Mitra Mandala Sobang by comparing two systems of availability. The aim of this research is to know the comparison system of the availability controlling that had been done by KUB Mitra Mandala Sobang using two systems of controlling the availability, namely Economic Order Quantity method (EOQ) and Just In Time method (JIT).After doing further analysis shows that in performing inventory control of raw materials, the costs incurred by KUB Mitra Mandala Sobang greater than using wide approach method Economic Order Quantity (EOQ) and the approach method of Just In Time (JIT). Meanwhile, if the approach of Economic Order Quantity (EOQ) compared with Just In Time (JIT), to use JIT approach is superior because the higher order quantity and total inventory costs lower